Toxicological Effects of Berberine and Sanguinarine - Singh, Nitika; Sharma, Bechan (Frontiers in Molecular Biosciences, 2018)
Berberine and Sanguinarine alkaloids belong to a group of naturally occurring chemical compounds that mostly contain basic nitrogen atoms. This group also includes some related compounds with neutral or weakly acidic properties. Alkaloids are produced by a large number of organisms including bacteria, fungi, plants, and animals. Berberine and Sanguinarine both are isoquinoline derivatives and belong to protoberberine and benzophenanthridines, respectively. Tyrosine or phenylalanine is common precursor for the biosynthesis of both. Sanguinarine [13-methyl (1,3) benzodioxolo(5,6-c)-1,3-dioxolo (4,5) phenanthridinium] is a toxin that kills animal cells through its action on the Na+-K+-ATPase transmembrane protein. Berberine, on the other hand, has been reported to cause cytotoxicity and adversely influence the synthesis of DNA. Several workers have reported varied pharmacological properties of these alkaloids as they exhibit antibacterial, antiasthma, anticancer, anti-inflammatory, and antidiabetic activities. This review article illustrates the toxicological effects of berberine and sanguinarine as well as mechanistic part of berberine and sanguinarine mediated toxicity in different living systems. This manuscript has included the lethal doses (LD50) of berberine and sanguinarine in different animals via different routs of exposure. Also, the effects of these alkaloids on the activities of some key enzymes, cell lines and organ development etc. have been summarized.